2014
DOI: 10.7314/apjcp.2014.15.17.7175
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Breast Health amongst Malaysian Female Adolescents

Abstract: Background: Breast cancer is the most common cancer among women in Malaysia, about one in 19 women being at risk. This study aimed to investigate knowledge and practice of breast self-examination (BSE), as well as knowledge of risk factors for breast cancer amongst female adolescents in Malaysia. Subsequently, relationships between demographic characteristics and knowledge level of BSE, risk factors for breast cancer and BSE practice were assessed. Materials and Methods: A descriptive, cross sectional survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 10 publications
2
30
0
1
Order By: Relevance
“…Similar to the finding of this study, Alsaif (2004) has reported that the majority of nursing students had performed BSE. In the previous studies it has reported that the incidence rate of female students performed BSE is low (Akhtari-Zavare et al, 2013;Al-Sharbatti et al, 2013;Che et al, 2014). Taking into consideration the fact that various factors play a role in urging individuals to have performed BSE like cultural beliefs, perception of health-disease, support of the family and social environment, belief in the importance of the applications which are required for early diagnosis of the disease (Nahcivan and Secginli, 2003;Cam and Gumus, 2006) we are pleased to see that the nursing students who are the subjects of this study had a high rate of having BSE done since this reflect that they have a high level of awareness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the finding of this study, Alsaif (2004) has reported that the majority of nursing students had performed BSE. In the previous studies it has reported that the incidence rate of female students performed BSE is low (Akhtari-Zavare et al, 2013;Al-Sharbatti et al, 2013;Che et al, 2014). Taking into consideration the fact that various factors play a role in urging individuals to have performed BSE like cultural beliefs, perception of health-disease, support of the family and social environment, belief in the importance of the applications which are required for early diagnosis of the disease (Nahcivan and Secginli, 2003;Cam and Gumus, 2006) we are pleased to see that the nursing students who are the subjects of this study had a high rate of having BSE done since this reflect that they have a high level of awareness.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the breast cancer accounts for 30-40 % of all the cancer incidences in women all over the world (Andsoy and Gul, 2014;Che et al, 2014;Rizalar et al, 2014). In Turkey, breast cancer incidence rates are rapidly increasing (Andsoy and Gul, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the studies determined the level of knowledge of breast cancer among Malaysian women based on several aspects such as general knowledge of breast cancer, causes, risk factors, symptoms of breast cancer and screening tests (Abdul-Hadi et al, 2010b;Khan et al, 2010;Akhtari-Zavare et al, 2011;Dahlui et al, 2012;Che et al, 2014;Yusof et al, 2014). Overall, females in Malaysia had a good awareness of breast cancer (AbdulHadi et al, 2010b;Khan et al, 2010;Akhtari-Zavare et al, 2011;Dahlui et al, 2011;Dahlui et al, 2012;Che et al, 2014;Yusof et al, 2014).…”
Section: Knowledge Of Breast Cancermentioning
confidence: 99%
“…Overall, females in Malaysia had a good awareness of breast cancer (AbdulHadi et al, 2010b;Khan et al, 2010;Akhtari-Zavare et al, 2011;Dahlui et al, 2011;Dahlui et al, 2012;Che et al, 2014;Yusof et al, 2014). Most respondents indicated that they heard about breast cancer mainly from sources such as books, magazines, brochures and television (Parsa and Kandiah, 2010;Al-Dubai et al, 2011;Akhtari-Zavare et al, 2013).…”
Section: Knowledge Of Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation